The Association of Occupational Psychosocial Factors with the Prevalence of Irritable Bowel Syndrome in the Chilean Working Population. Issue 4 (16th March 2019) - Huerta, Patricia A; Cifuentes, Manuel; Levenstein, Charles; Kriebel, David
Abstract: Background: Irritable bowel syndrome (IBS) is a stress-related disease linked to psychosocial factors, though knowledge about its occupational psychosocial aspects is scarce. Objective: A cross-sectional study of the prevalence of IBS and its association with occupational psychosocial factors in Chilean workers was conducted. Methods: IBS prevalence, using the IBS-Rome IV criteria, in the working population was estimated using data from the National Health Survey of 2009. Data on occupational psychosocial aspects were drawn from the Chilean Survey of Employment, Health, and Work of 2009, and allocated to individual survey participants at the occupation–region level. Data on family and community stressors were available at the individual level. Prevalence ratios (PR) for IBS were computed using generalized linear mixed models to account for variability at the group level. Results: The IBS prevalence in the overall working population (weighted n = 5 435 253) was 18.4%, but varied substantially by industry sector. Compared with 'professionals' (IBS prevalence = 7.3%), jobs with high prevalence of IBS included 'health and social work activities' [PR = 4.9; 95% confidence interval (CI) = 1.4–16.7], 'household employment' (PR = 4.8; 95% CI = 1.5–15.9), and 'manufacturing' (PR = 3.5; 95% CI = 1.0–11.8). With Karasek Job Demand Control scores assigned to occupations within regions, high job demand doubled the prevalence of IBS (PR = 2.0; 95% CI = 1.4–2.9), whereas high-skill discretion was associated with lower prevalence of IBS (PR = 0.6; 95% CI = 0.4–0.8). There was also evidence that these two factors were not independent; high-skill discretion appeared to buffer the effect of high job demand on IBS prevalence ( P < 0.001). Conclusions: Occupational factors were associated with IBS prevalence, showing effects as important as those for non-occupational stresses such as civic insecurity or having health problems. High job skill discretion appeared to reduce the prevalence of IBS in the presence of high job demands. Given its high overall prevalence and poorly understood risk factors, further research on occupational psychosocial factors of IBS is warranted.